Pengaruh Model Pembelajaran Survey, Question, Read, Recite, Reflect, Review (SQ4R) terhadap Motivasi Belajar Siswa - Diora Gustina; Tontowi Amsia; Yustina Sri Ekwandari (FKIP UNIVERSITAS LAMPUNG, 2018)
The purpose of this research is to find out the influence of Survey, Question, Read, Recite, Reflect, Review (SQ4R) learning model on students' learning motivation in History subject for students of grade XI Social Science class of Senior High School 1 Banjit academic year of 2017/2018. This research applied One Group Pretest-Posttest Design as its research design. The population in this research was taken from students of grade XI Social Science class Senior High School 1 Banjit. The sample of the research was carried out using Saturated Sampling technique. The data analysis technique was done through quantitative data analysis with Theta formula. The result showed that from the quantitative data analysis using the Theta formula, it can be concluded that: